CORPORATE GOVERNANCE, PROFITABILITAS, SOLVABILITAS, DAN AUDIT REPORT LAG - Clarissa Maya Devi (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2022)
Companies that go public have an obligation to submit financial reports that have been audited by a public accountant on a regular and timely basis. Information from financial reports that is submitted in a timely manner is useful for stakeholders to make investment decisions. Information from financial reports is new, accountable, relevant and transparent. However, time constraints are one of the main factors that financial reports cannot be submitted on time (audit report lag). Audit report lag is the length of time from the closing date of the company's fiscal year to the date of the auditor's report. This study aims to determine the effect of corporate governance (proxied by audit committee meetings and audit committee of accounting experts), profitability and solvency on audit report lag in manufacturing companies listed on the Indonesia Stock Exchange for the 2017-2019 period. The sampling technique was purposive sampling method and the type of data used was quantitative data. The total number of companies that were sampled in the research data were 76 manufacturing companies. The results of descriptive statistics show that the average delay in submitting financial reports and audit reports in 2017-2019 is 71.22 days. The results of this study indicate that partially the audit committee of accounting expert variable affects the audit report lag. Meanwhile, the audit committee meeting variables, profitability, and solvency did not affect the audit report lag. Based on the simultaneous statistical test, it shows that the variables of the audit committee meeting, audit committee of accounting expert, profitability, and solvency have an effect on the audit report lag.